Structure of Macrozoobenthos Community in Mangrove Eco-Tourism Area of Pantai Merdeka Bagan Kuala Tj. Beringin Serdang Bedagai District North Sumatra - Yunita Amelinda Harahap; Melfa Aisyah Hutasuhut (Jurnal Penelitian Pendidikan IPA, 2025)
The mangrove ecosystem serves as a protector of coastal areas from the onslaught of currents and waves, as a habitat, for foraging, and as a breeding ground for various organisms and others. This research aims to determine the relationship between mangrove vegetation density and macrozoobenthos abundance in the ecotourism area of the Mangrove Forest of Pantai Merdeka Bagan Kuala Tj Beringin Serdang Bedagai. Data collection was conducted using survey methods with quadrat transects for collecting data on mangrove vegetation and macrozoobenthos at three observation stations. Based on the observation results, the composition of mangroves in the ecotourism area consists of Rhizopora sp. (52.90%), Avicennia sp. (23.50%), and Sonneratia sp. (23.50%) with higher mangrove vegetation density (140.100-150.79 ind/ha), thus falling into the good condition criteria. The identification results of macrozoobenthos showed there were 27 species consisting of: 16 species from the class Gastropoda, 2 species from the class Malacostraca, 5 species from the class Bivalvia, 2 species from the class Polychaeta, 1 species from the class Holothuroidea, and 1 species from the class Amphipoda. The abundance of macrozoobenthos in mangrove forests ranges from 85 ind/m2 to 204 ind/m2. The diversity index is moderate to high, and the evenness indicates that the macrozoobenthos community is relatively stable with values between 0.60-0.85. The relationship between mangrove vegetation density and macrozoobenthos abundance is categorized as very strong with a correlation value of 0.92.